The Mechanism of Melanocytes-Specific Cytotoxicity Induced by Phenol Compounds Having a Prooxidant Effect, relating to the Appearance of Leukoderma. (12th March 2015) - Nagata, Takeshi; Ito, Shinobu; Itoga, Kazuyoshi; Kanazawa, Hideko; Masaki, Hitoshi
Abstract : Specific phenol compounds including rhododendrol (RD), a skin-brightening ingredient in cosmetics, are reported to induce leukoderma, inducing a social problem, and the elucidation of mechanism of leukoderma is strongly demanded. This study investigated the relationship among the cytotoxicities of six phenol compounds on B16F10 melanoma cells and HaCaT keratinocytes and generated reactive oxygen species (ROS). As a result, the cytotoxicity of RD on B16F10 cells was higher than that on HaCaT cells, and RD significantly increased intracellular ROS and hydrogen peroxide (H2 O2 ) levels in B16F10 cells. Furthermore, although raspberry ketone (RK), RD derivative, also increased intracellular ROS in B16F10 cells, increase in ROS was suppressed by disodium dihydrogen ethylenediaminetetraacetate dehydrate (EDTA). The amounts of increased ROS with RK in HaCaT cells without melanocyte were further increased by tyrosinase. Therefore, tyrosinase, a metalloprotein having copper, was speculated to be one of causative agents allowing phenol compounds to work as a prooxidant. Hydroxyl radical was generated by adding a mixture of tyrosinase and H2 O2 to RD, and the amount of the radical was further increased by UVB, indicating that RD cytotoxicity was caused by intracellularly increased ROS, which possibly related to phenol induced prooxidants.